DESCRIPTION OF STUDENTS' FRACTION PROBLEM-SOLVING ABILITY BASED ON KEIRSEY'S PERSONALITY TYPE : DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH PECAHAN SISWA DITINJAU DARI TIPE KEPRIBADIAN KEIRSEY - Talib, Ahmad; Rosidah; Asmaun; Rismayanti; Sri Yuyun (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
Abstrack: This research aims to describe the problem-solving ability of fractional counting operations in terms of Keirsey's personality type. The type of research is qualitative research with a descriptive approach. The research subjects were 4 students from class VII A of SMPN 18 Selayar with 1 subject for each personality type. The research instruments used personality type classification instruments, problem-solving tests, and interview guides. The results of the research show that 1) Students with the guardian personality type are able to understand the problem, make a solution plan, carry out the solution plan, and check again, 2) Students with the artisan personality type are able to understand the problem, make a solution plan for problem 1 but are unable to solve problem 2, unable to carry out the solution plan and unable to check again, 3) Students with the rational personality type are able to understand the problem, make a solution plan for problem 1 but are unable to solve problem 2, carry out the solution plan, and check again, 4) ) Students with the idealist personality type are able to understand the problem, make a plan to solve problem 1 but are not able to solve problem 2, and also unable carry out the solution plan, as well as to check again.